Laser versus dermabrasion and split thickness skin graft for management of post burn leucoderma - Gad, Shawki S.; Kishk, Tarek F.; Taalab, Ahmed A.; Gerza, Ahmed I. El (International Surgery Journal, 2019)
Background: The aim of the study is to compare between dermabrasion and split thickness skin grafting and fractional CO2 laser in management of post burn leucoderma. Deep burn can have serious aesthetic consequences as it often result in scar tissue and pigmentary changes in the skin. It is understood that skin pigmentation involves melanin. Leucoderma results from melanin loss at the basal layer of the epidermis. Fibrosis ultimately inhibits melanocyte migration and subsequent production of melanin in the injured area. Management of post burn leucoderma was either non-surgical or surgical treatment. Non-surgical therapies are make-up, tattooing and fractional CO2 laser. The surgical treatments include dermabrasion with thin split thickness skin grafting, non-cultured keratinocyte-melanocyte suspensions, mini grafting, cultured epithelium, blister epidermal grafting, chip skin grafting and epidermal cell suspension spray. Methods: A prospective study of 30 patients with post burn leucoderma between May 2018 and May 2019, at Ahmed Maher Teaching Hospital. Dermabrasion and split thickness skin grafting in 15 patients (group 1). Fractional CO2 laser in another 15 patients (group 2). Results: Group one: 13% of patients showed excellent colour match, 33% good colour match and 53% poor colour match. Group two: 27% of patients showed excellent colour match, 47% good colour match and 26% poor colour match (p value=0.311). Conclusions: Fractional CO2 laser is better than dermabrasion and STSG for management of post burn leucoderma.